Daños mecanicos producidos por Xylotrechus arvicola (OLIVIER, 1795)(Coleoptera: Cerambycidae) - Armendariz, I.=700 1 Juarez, J.S; campillo, G.; Perez-Sanz, A.; Miranda, L.
(Es, En)
Ilus., 20 ref.
Keywords: XYLOTRECHUS; COÑEOPTERA; CERAMBYCIDAE; DAÑOS; VID; ESPAÑA; TORNILLO DE LA VID; DAÑOS MECANICOS; BOLETIN DE SANIDAD VEGETAL: PLAGAS